Measurement of the CKM angle γ using the B± → D*h± channels - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2023)
A measurement of the CP-violating observables from B± → D*K± and B± → D*π± decays is presented, where D*(D) is an admixture of D*0 and $$ {\overline{D}}^{* 0} $$(D0 and $$ {\overline{D}}^0 $$) states and is reconstructed through the decay chains D* → Dπ0/γ and $$ D→ K_S^0π^{+}{π}^{-}/K_S^0K^{+}{K}^{-} $$. The measurement is performed by analysing the signal yield variation across the D decay phase space and is independent of any amplitude model. The data sample used was collected by the LHCb experiment in proton-proton collisions and corresponds to a total integrated luminosity of 9 fb−1 at centre-of-mass energies of 7, 8 and 13 TeV. The CKM angle γ is determined to be $$ {\left({69}_{-14}^{+13}\right)}^{° } $$using the measured CP-violating observables. The hadronic parameters $$ {r}_B^{D^{* }{K}^{± }},{r}_B^{D^{* }{π}^{± }},δ_B^{D^{* }{K}^{± }},δ_B^{D^{* }{π}^{± }} $$, which are the ratios and strong phase differences between favoured and suppressed B± decays, are also reported.
*The LHCb collaboration: R. Aaij, S. Bachmann, D. Berninghoff, M. Borsato, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, G. Tuci, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Im Titel sind das Plus-, Minus- und Asterix-Zeichen hochgestellt
Gesehen am 03.07.2024